Right heart failure after left ventricular assist device implantation: latest insights and knowledge gaps on mechanism and prediction - Nonaka, Hideaki; Lu, Lawrence Y.; Obonyo, Nchafatso G.; Suen, Jacky Y.; McGiffin, David C.; Fanning, Jonathon P.; Fraser, John F. (Frontiers in Cardiovascular Medicine, 2025)
Heart failure is a global health concern, with many patients being unresponsive to medical therapies. In end-stage disease, left ventricular assist devices (LVADs) offer an alternative to transplantation, yet their clinical course remains unfavorable, with up to one in four patients dying within a year. Although LVAD implantation aims to alleviate left-sided congestion and reduce right ventricular burden, a significant proportion of patients develop RHF, which is a major driver of morbidity and mortality. The underlying mechanisms leading to RHF remain a subject of debate, with no definitive conclusions reached. Due to the heterogeneity of heart failure pathophysiology, clinical data varies, and the translation of preclinical findings into effective bedside management remains challenging. These factors collectively hinder the precise characterization of RHF mechanisms, with some proposed explanations remaining speculative. Assessing the risk of RHF development based on pathophysiological insights is essential. However, predicting the progression of RHF following LVAD implantation remains difficult due to complex hemodynamic interactions and the lack of established guidelines, often leading to missed opportunities for timely right ventricular (RV) support device implantation. To reduce the incidence of RHF, this review aims to provide insights into RV failure mechanisms and propose a refined predictive approach. Although data in this field is rapidly evolving, explanations and assessment methods have not been significantly updated. This paper consolidates recent findings, presents updated perspectives, and identifies remaining gaps in knowledge.